1991
DOI: 10.1093/oxfordjournals.aje.a115870
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Distribution in Relation to Physical Activity and Smoking Habits in 38-year-old European Men

Abstract: The authors studied 512 European men all born in 1950 from six different towns in the period October 1988 to May 1989. Anthropometric measurements were taken, including weight, height, and circumferences (waist, hip, thigh). Educational level, activity scores and information on smoking habits were obtained from a questionnaire. Higher educational level was associated with lower body mass index, waist/hip ratio, and waist/thigh ratio. The sports activity score was negatively related to waist/hip ratio (beta +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
72
3
2

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 0 publications
10
72
3
2
Order By: Relevance
“…Our observation that physical inactivity was associated independently with abdominal obesity among the 31-y-old men is in line with earlier reports (Seidell et al, 1991), while a similar relation was detected for women in the first logistic regression model, but when BMI at 31 y was included in the analysis the OR for abdominal obesity decreased somewhat with a lower limit of 0.97 for the 95% CI. This can be explained by the close correlation of overweight and obesity, the most important predictors of abdominal obesity, with physical inactivity, so that a high BMI will reduce the independent effect of physical inactivity in the logistic regression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observation that physical inactivity was associated independently with abdominal obesity among the 31-y-old men is in line with earlier reports (Seidell et al, 1991), while a similar relation was detected for women in the first logistic regression model, but when BMI at 31 y was included in the analysis the OR for abdominal obesity decreased somewhat with a lower limit of 0.97 for the 95% CI. This can be explained by the close correlation of overweight and obesity, the most important predictors of abdominal obesity, with physical inactivity, so that a high BMI will reduce the independent effect of physical inactivity in the logistic regression.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier findings on the effect of alcohol intake on abdominal obesity have not been consistent (Sakurai et al, 1997;Dallongeville et al, 1998;Lahmann et al, 2000). Similarly, some authors have observed that smoking is associated with abdominal obesity (Seidell et al, 1991), which was not found here. On the other hand, smoking is often associated with high alcohol consumption (Kesse et al, 2001), and this may at least partly explain the controversial findings regarding alcohol intake, smoking and abdominal obesity.…”
Section: Discussioncontrasting
confidence: 59%
“…Very few studies have combined the level of physical activity and nutritional habits in predicting an unhealthy physical status. Moreover, in spite of the considerable interest at this moment in the issue of regional fat pattern in the prediction of disease risk, 31 there are few studies that include other indicators of health-related anthropometry besides the body mass index. Another important feature of this study is the use of different categories of physical activity (occupational, active and total) including activity that is of low intensity and habitual.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have not been population-based or have only investigated a very limited age range. 9 Also, different methods for measuring the circumferences have been applied. As a result, whereas the distribution of overall obesity in different populations is well documented in the literature, 10,11 little is known about the distributions of waist and hip circumferences and the WHR, among populations in different countries with varying degrees of overweight.…”
Section: Introductionmentioning
confidence: 99%